O desenvolvimento profissional corresponsável na formação de professores de língua materna à luz da Teoria Holística da Atividade - Kist, Liane Batistela (2017)
This study investigates the Co-responsible Professional Development (DPC, in Portuguese), in first language teachers’ formation (LM teachers, in Portuguese) based on the Holistic Activity Theory (THA, in Portuguese). The DPC is a triadic conception of professionalization that articulates, based on alliance and reciprocal confidence, three contexts: Academy, Graduation and Market. The DPC is one of the basic concepts of THA studied by Richter (2011) which pattern concerns on the inseparability among conduct, concept and quality in the professional practice, ordered in a systemic way through a set of criteria that are the basis of the parameterization of a specialized job in an autopoietic horizon, denominated as framework. The development of the investigation starts out from an analysis from an excerpt of the activity report of the Portuguese Language Course Subproject that integrates the Institutional Scholarship Program of Introduction to Teaching First Language (PIBID/Português, in Portuguese). Owing that, to implement a DPC, a professional alliance is necessary based on a link of confidence and on the adoption of a paradigm of consensual work (framework) between initial and in-service capacitation, this study begins by analyzing the PIBID/Português as a formative model able to anchor the necessary elements to the professional development of first language teachers. Through a case study within the scope of qualitative research and using the indiciary paradigm from GINZBURG (1989), it is possible to say, in a general way, that PIBID/Português revealed itself as a formative referential with a strong tendency to anchor a DPC and its developments: principles of job framework founded by the DPC, absence of problems in the framework interfaces, setting up as a consequence of the absence of deviation in the means and relations with the socio-interacionist paradigm in the conceptual field of first language, which are revealers of what THA denominates as overcoming akrasia. In other words, this study brings out some positive aspects concerning the inseparability between conduct, concept and value in a triadic situation of professionalization.